The Efficacy of Mnemonic Strategies in Improving the Basic Multiplication Facts Retrieval - Wulandary, Verra; Kawai, Norimune (Angstrom Centre of Education, 2024)
The current quasi-experimental study aims to investigate the efficacy of mnemonic strategies (Visual imagery and Story-linking) to improve the basic multiplication fact retrieval of grade 3 students with mathematics difficulties. The authors employed a quantitative approach within the matching-only pretest-post-test control group design to analyze the data on 206 subjects, of whom 78 exhibited mathematical difficulties. The study was conducted in eight inclusive primary schools in Purwakarta City, Indonesia. The research findings indicated that the N-gain acquisition of students in the experimental group (0.38) outperformed students in the control group (0.11). Similarly, the N-gain acquisition of students with mathematics difficulties in the experimental group (0.26) indicated a higher enhancement than those in the control group (0.08). Overall, the mnemonic strategies improved the students’ retrieval of basic multiplication facts on students with and without mathematics difficulties. However, mnemonic strategies have successfully achieved two of the Sustainable Development Goals 4 (SDG 4) by the 2030 Agenda for Sustainable Development on ensuring students with disabilities as one of the vulnerable groups, have equal access to education and guaranteeing both male and females are literate and numerically literate. These findings have practical implications for educators, providing them with actionable insights to develop effective teaching strategies for students with mathematics difficulties.